The Impact of Entrepreneurial Strategy on the Firm Performance of Indonesian Technology Startups - Triono, Sunu Puguh Hayu; Rahayu, Agus; Wibowo, Lili Adi; Alamsyah, Andry (Jurnal Manajemen Indonesia, 2024)
Changes in the business environment, driven by technology and globalization, increase the urgency of a strategic orientation for new ventures and, conversely, an entrepreneurial orientation for established firms. Technology startups, as "innovation machines," face unique challenges related to the environment, competition, and resource limitations. Therefore, they need to be more strategic in conducting their business. Entrepreneurial strategy is a new strategic framework specifically formulated for startups. However, the effect of this strategy on firm performance has not been confirmed. This study investigates the relationship of entrepreneurial strategy on the tech startup’s firm performance. A conceptual model was developed based on the strategic management framework, including strategy formulation, implementation, and evaluation. The data was collected via an online survey and was able to gather 39 respondents, dominated by the fields of SaaS, Edutech, and health tech. The data was then analyzed using SmartPLS software. The analysis showed that entrepreneurial strategy has a positive effect on firm performance, value offering (value-based strategy), and innovation ambidexterity. Further analysis found that there was no significant mediation effect or indirect relationship. Additionally, the predictability analysis found that the structural model in this study has moderate predictability power. The results of this study contribute to the strategic entrepreneurship field by providing evidence of how entrepreneurial strategy can improve tech-startup firm performance. Lastly, the limitations in this study can provide new opportunities for future research, especially related to objects, operationalization, and conceptual models. Keywords— Entrepreneurial Strategy; Innovation Ambidexterity; Offered Value; Startup’s Firm Performance; Strategic Entrepreneurship